Penguatan Kepedulian Sosial Melalui Kegiatan Keagamaan di Pandan Katsuri Kecamatan Sirimau Kota Ambon Maluku - Rizki Muhammad Ramdhan; Asep; Bahasoan, Aminah; Rena Yuliana (Jurnal Nusantara Berbakti, 2023)
Understanding and respecting each other is the nature that should be carried out in society. Character is a personality that is driven by various things, one of which is through faith. Community service activities carried out with the aim of strengthening social care through religious activities are carried out through community education methods by collaborating with religious leaders. Service activities are carried out through 4 stages, namely, 1) Socialization, 2) Coordination, 3) Implementation, and 4) Evaluation. community service activities that are integrated with religious activities provide opportunities for the community to deepen religious knowledge. Through religious activities carried out in the context of character building, it provides an understanding for the community to understand each other in the form of social care. Social care is formed when there is an ability to understand oneself and provide a positive reflection to understand the situation around. The hope is that this religious activity can become a routine program that is carried out on an ongoing basis